MOTIVATIONAL PROFILES IN LOCAL SPORT CENTERS - Sicilia Camacho, Álvaro; Águila Soto, Cornelio; Muyor Rodríguez, José Mª; Orta Cantón, Antonio; Moreno Murcia, Juan Antonio (Anales de Psicología / Annals of Psychology, 2009)
The purpose of this paper was to detect motvational profiles in local sport centres. Based on self-determination theory (Deci y Ryan, 1985, 1995, 2001) and the Vallerand’s integrated proposals (1997, 2001), it was expected that at least two motivational profiles would emerge: a self-determined profile and a conditioned motivationally profile toward physi-cal activity. In order to reach the purpose of this study, questionnaires were administered to 727 users, aged between 14 and 78 years, from two local sport centers. A cluster analysis produced two motivational profiles which were rep-licated in the second sport center. The first cluster was named the ‘self-determined profile’ because the users reported higher level of self-determined motivation, perception of task-involving climate, incremental belief, perceived competence and perception of autotelic experience than the second of motivational profiles. The second cluster was named the ‘conditioned motivationally profile’, with a higher external motivation and desmotivation than the first one and also higher scores on perception of ego-involving climate and entity belief. Furthermore, a chi square analysis showed that the formation of both profiles were widely determined by the user’s previous practice in physical activity. The results demonstrate the importance of developing competence, incremental belief and self-determination, as it was associated with high level of perceived autotelic experience and other adaptative patterns which empowerment the adher-ence to physical activity.